FROST PROTECTION MEASURES: SURVEY RESULTS - Fike, Matej; Smrekar, Miha; Fekonja, Mateja (Journal of Energy Technology, 2023)
In Slovenia, frosts occur often and it causes great damage for growers. Various passive and active methods are known for frost protection. Pasive methods can be implemented throughout the year. They are used to enable easier implementation of active methods, which are in use when a period of frost occurs. The aim of this research is, with the help of a survey, to assess whether growers in Slovenia implement active or passive methods of frost protection, and if not, why not. The survey contained 24 questions and was intended primarily for fruit and wine growers in Slovenia. The results of the survey show that frost happens to Slovenian growers on average every other year, and destroys on average 50% of their crop. Despite frequent frosts and the damage they cause, growers are not implementing any active measures, nor are they willing to invest in them. The reasons for this may be the large investments required for active measures, the small sizes of farms in Slovenia (on average 12 ha according to the survey answers), or that farmers are insufficiently informed about the various measures.